Решить уравнение (3x+1)(x-1)-2x=(x+2)-5

pandapurple pandapurple    2   26.07.2019 22:20    0

Ответы
uroolga uroolga  03.10.2020 13:46
3xx-3x*1+1x-1-2x=x+2-5
3x^2-5x+2=0
x1=1 x2=2/3
ПОКАЗАТЬ ОТВЕТЫ
kotovad444 kotovad444  03.10.2020 13:46
Раскроем скобки
3x^{2} -3x+x-1-2x=x+2-5

Переносим всё в одну сторону и сокращаем что можем.
3 x^{2} -4x-1-x+3=0

3 x^{2} -5x-2=0

D=(-5)^2-4*3*2=1

 x_{12} = (5+-1)/2*3 = \left \{ {{x_{1} =6/6=1} \atop { x_{2} =4/6=2/3}} \right.


ответы: 2/3 и 1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика